The two Josephson junction flux qubit with large tunneling amplitude - Shnyrkov, V.I.; Soroka, A.A.; Melnyk, S.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
In this paper we discuss solid-state nanoelectronic realizations of Josephson flux qubits with large tunneling amplitude between the two macroscopic states. The latter can be controlled via the height and form of the potential barrier, which is determined by quantum-state engineering of the flux qubit circuit. The simplest circuit of the flux qubit is a superconducting loop interrupted by a Josephson nanoscale tunnel junction. The tunneling amplitude between two macroscopically different states can be essentially increased, byengineering of the qubit circuit, if tunnel junction is replaced by a ScS contact. However, only Josephson tunnel junctions are particularly suitable for large-scale integration circuits and quantum detectors with preset-day technology. To overcome this difficulty we consider here the flux qubit with high-level energy separationbetween «ground» and «excited» states, which consists of a superconducting loop with two lowcapacitance Josephson tunnel junctions in series. We demonstrate that for real parameters of resonant superposition between the two macroscopic states the tunneling amplitude can reach values greater than 1 K. Analytical results for the tunneling amplitude obtained within semiclassical approximation by instanton technique show good correlation with a numerical solution.